Prognostic Value of Functional Capacity in Different Exercise Protocols. Issue 13 (7th July 2020) - Harb, Serge C.; Bhat, Pavan; Cremer, Paul C.; Wu, Yuping; Cremer, Laura J.; Berger, Stephanie; Cho, Leslie; Menon, Venu; Gulati, Martha; Jaber, Wael A.
Abstract : Background: Functional capacity is associated with mortality, although the prognostic value of achieved estimated metabolic equivalents (METs) across various exercise protocols is not established. We sought to determine whether achieved METs had different prognostic implications according to the protocol employed. Methods and Results: From 1991 to 2015, we identified 120 705 consecutive patients from a stress testing registry who underwent the following 7 different standardized exercise protocols: Bruce, modified Bruce, Cornell 0%, Cornell 5%, Cornell 10%, Naughton, and modified Naughton. The primary outcome was all‐cause mortality. There were 74 953 Bruce, 8368 modified Bruce, 2648 Cornell 0%, 9972 Cornell 5%, 20 425 Cornell 10%, 1226 Naughton, and 3113 modified Naughton protocols. During a mean follow‐up of 8.7 years, a total of 8426 deaths (6.9%) occurred. When compared with the Bruce protocol, after multivariable adjustment for clinical risk factors, medications, and functional capacity, test protocol was independently associated with mortality (modified Naughton [hazard ratio (HR), 2.51; 95% CI, 2.26–2.8], Naughton [HR, 1.79; 95% CI, 1.57–2.04], Cornell 0% [HR, 1.79; 95% CI, 1.59–2.01], modified Bruce [HR, 1.62; 95% CI, 1.48–1.76], Cornell 5% [HR, 1.61; 95% CI, 1.47–1.75], and Cornell 10% [HR, 1.32; 95% CI, 1.22–1.42]). Across all protocols, higher estimated METs were associated with lower mortality, although the equivalent METs achieved were associated with a worse prognosis in less‐demanding protocols. Conclusions: Higher estimated METs are reliably associated with lower mortality in all exercise protocols, although the prognostic value is not transferable across different tests. Consequently, the prognostic value of METs achieved during a stress test should be considered protocol dependent.